EFEKTIVITAS MODEL FLIPPED CLASSROOM BERBANTUAN VIDEO PENDEK TIKTOK-STYLE DALAM MENINGKATKAN MOTIVASI BELAJAR SEJARAH KEBUDAYAAN ISLAM DI MTS KHA WAHID HASYIM BANGIL - Ahmad Aris Fajarudin; Fitri Kurnia; Nailatul Khoriyah Cholil (As-Sulthan Journal of Education, 2026)
This study examines the effectiveness of a TikTok-style short video-assisted flipped classroom model on students' learning motivation in Islamic Cultural History (SKI) at MTs KHA Wahid Hasyim Bangil. Low motivation, driven by lecture-dominant teaching and a mismatch between instructional style and Generation Z learners' digital characteristics, served as the primary background. Using a quasi-experimental non-equivalent control group design, the study involved 64 eighth-grade students divided equally into experimental and control groups (n=32 each). A motivation instrument based on Keller's ARCS model was employed (α = 0.891). Results showed the experimental group achieved an N-Gain of 0.55 (moderate), compared to 0.28 (low) in the control group. An independent t-test yielded a significance value of 0.000 (p < 0.05), confirming a significant difference between groups. The Attention dimension showed the greatest improvement. This study offers an innovative approach integrating popular media formats into Islamic education at the junior secondary level.